2009
DOI: 10.1163/156856809789476074
|View full text |Cite
|
Sign up to set email alerts
|

Representation of space: image-like or sensorimotor?

Abstract: We investigate the relation between the physical world and its mental representation in the 'cognitive map', and test if this representation is image-like and complies with the laws of Euclidean geometry. We have developed a new experimental technique using 'impossible' virtual environments (VE) to directly influence the representational development. Subjects explore a number of VEs -- some 'normal', others with severe violations of Euclidean metrics or planar topology. We check if these manipulated properties… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(18 citation statements)
references
References 37 publications
0
18
0
Order By: Relevance
“…While related strategies have been demonstrated in other navigation and route selection studies (e.g., Golledge, 1995;Bailenson, Shum, & Uttal, 2000;Conroy Dalton, 2003), it remains unclear why participants chose the option with the longest line of sight. A possible explanation is that this path option promises greater information gain when traveling along than the alternative (Zetzsche et al, 2009). However, further research is needed to investigate this behavior.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While related strategies have been demonstrated in other navigation and route selection studies (e.g., Golledge, 1995;Bailenson, Shum, & Uttal, 2000;Conroy Dalton, 2003), it remains unclear why participants chose the option with the longest line of sight. A possible explanation is that this path option promises greater information gain when traveling along than the alternative (Zetzsche et al, 2009). However, further research is needed to investigate this behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Authors like Zetzsche, Galbraith, Wolter, and Schill (2009) argue that weaker representation of environments such as route-level knowledge about landmarks and connections between them (cf. Siegel & White, 1975), are often sufficient for successful wayfinding (see also Gillner & Mallot, 1998).…”
Section: Synopsismentioning
confidence: 99%
“…This resonates with the vast amount of evidence pointing to the supportive effects of active physical movement and idiothetic cues (Klatzky et al, 1998;Wraga et al, 2004), as well as notions of embodiment (Mallot & Basten, 2009;Wilson, 2002). How we perceive our environment, and how we interact with it, is affected fundamentally by basic sensorial information derived directly from our physical immersion in the environment (Zetzsche, Wolter, & Schill, 2008;Zetzsche et al, 2009). Accordingly, there are natural limits to what VR without actual motion can achieve as a tool for research in spatial cognition (Taube, Valerio, & Yoder, 2013).…”
Section: Discussionmentioning
confidence: 63%
“…These mechanisms are at work across real-world and virtual navigation scenarios; however, performance is only at its best given full availability of sensorimotor input (Zetzsche, Galbraith, Wolter, & Schill, 2009). Longer reaction times in virtual desktop scenarios (cf.…”
Section: Navigation and Orientation In Real And Virtual Environmentsmentioning
confidence: 99%
“…Instead of an imagelike metric map, people rely on what appears to be a gradually acquired collage of different kinds of knowledge [36]. Because metrically or topologically impossible environments do not deter people [41], neurophysiologists have suggested that human mental models remove perceived but irrelevant details [11]. For clarity, additional related cognitive work is cited in the next section.…”
Section: Related Workmentioning
confidence: 99%